The Characteristic Use of the Plural in Modern Arabic - Mujič, Muhamed A. (Prilozi za orijentalnu filologiju, 2017)
In attempting a contrastive analysis of Arabic and Serbo-Croat, the author points to characteristic ways in which the plural is used, above all, at the level of syntax. All the cases cited represent specific lingvistic forms for the foreign student and certainly for anyone whose mother tongue is Serbo-Croat. The characteristic plural form under discussion appears in the following cases: a) when the plural form is used with the preposition min; b) when. the plural form is used in annexation; c) in the use of the plural form in some common expressions in modem Arabic in connection with politics and economics. The author has quoted numerous examples to illustrate the above usages, corroborating those under point' e' with quotations from the daily press.